Researchers' Seedbeds for the Development of Research Skills in Universities - C. Rodríguez-Vargas, Martha; O. Alcázar-Aguilar, Oscar; L. Gil-Cueva, Silvia; Garay-Argandoña, Rafael; M. Hernandez, Ronald (International Journal of Criminology and Sociology, 2022)
The objective of this study is to demonstrate the effects of the application of the pedagogical strategy "researcher's seedbed" in the development of research skills in universities. This research is of quasi-experimental, longitudinal and prospective design, where 2 groups were formed: control and experimental, of 18 students each. A validated instrument was used to measure the research competences, as well as a rubric for the evaluation of the research projects. It began with a pre-test, and after 14 weeks of the development of the strategy, through different educational sessions, the post-test was administered. Likewise, the research projects carried out were evaluated. The results obtained showed that the pedagogical strategy had a positive effect on the development of research skills, with the highest evaluation being found in 40% of the students, with statistically significant differences between the control and experimental groups (Mann Whitney U, p=0.007), and between the pre-test and post-test (Wilcoxon, p=0.00). In the development of cognitive and procedural competence, an effect was also found in the strategy, but not in the attitudinal competence (Mann Whitney U, p=0.496). The application of this study is based on the fact that the formation of research groups in universities strengthens formative research in higher level students. This study shows the benefits of the implementation of strategies for the development of research competencies, since the product will be to train professionals with a scientific culture in favor of society.